Quantification of Intact O-Glycopeptides on Haptoglobin in Sera of Patients With Hepatocellular Carcinoma and Liver Cirrhosis - Shu, Hong; Zhang, Lei; Chen, Yiwei; Guo, Yijie; Li, Limin; Chen, Fanghua; Cao, Zhao; Yan, Guoquan; Lu, Chunlai; Liu, Chao; Zhang, Shu (Frontiers in Chemistry, 2021)
Haptoglobin (Hp) is one of the acute-phase response proteins secreted by the liver and its aberrant N-glycosylation was previously reported in hepatocellular carcinoma (HCC). Limited studies on Hp O-glycosylation have been previously reported. In this study, we aimed to discover and confirm its O-glycosylation in HCC based on lectin binding and mass spectrometry (MS) detection. First, serum Hp was purified from patients with liver cirrhosis (LC) and HCC, respectively. Then, five lectins with Gal or GalNAc monosaccharide specificity were chosen to perform lectin blot and the results showed that Hp in HCC bound to these lectins much stronger than that in LC. Furthermore, label-free quantification based on MS was performed. A total of 26 intact O-glycopeptides were identified on Hp and most of them were elevated in HCC as compared to LC. Among them, the intensity of HYEGS316TVPEK (H1N1S1) on Hp was the highest in HCC patients. Increased HYEGS316TVPEK (H1N1S1) in HCC was quantified and confirmed using MS method based on 18O/16O C-terminal labelling and Multiple Reaction Monitoring. This study provided a comprehensive understanding of the glycosylation of Hp in liver diseases.